Menafsirkan Cinta Melalui Tanda: Analisis Semiotika Saussure Pada Lagu Arab Tamalli Ma'ak Karya Amr Diab - Rahmat Mulya Nugraha; Alwah Asaniah (Program Studi Pendidikan Bahasa Arab Universitas Nahdlatul Ulama Purwokerto, 2025)
The background of this research focuses on the song Tamalli Ma'ak by Amr Diab, which is famous for its meaningful and emotional lyrics. The purpose of this study is to identify and analyze the sentences in the lyrics of Tamalli Ma'ak that illustrate the theme of love and longing. This song was chosen as the object of study because of its ability to convey deep feelings through simple yet powerful language. Using Ferdinand de Saussure's semiotic approach, this research analyzes the relationship between signifier and signified in the lyrics, which function as signs with hidden meanings. The results show that the lyrics of Tamall Ma'ak are not only a linguistic aesthetic expression, but also reflect strong emotional longing and commitment, depicting emotional attachment despite being physically separated. Through semiotic analysis, it was found that these lyrics depict the power of love that is eternal and transcends the boundaries of space. The findings are expected to provide readers with new insights into how language in music can be used as a means to convey complex feelings, as well as enrich semiotic studies in the context of Arabic popular music.